Comparative Genomic Hybridization Selection of Blastocysts for Repeated Implantation Failure Treatment: A Pilot Study. (23rd March 2014) - Greco, Ermanno; Bono, Sara; Ruberti, Alessandra; Lobascio, Anna Maria; Greco, Pierfrancesco; Biricik, Anil; Spizzichino, Letizia; Greco, Alessia; Tesarik, Jan; Minasi, Maria Giulia; Fiorentino, Francesco
Abstract : The aim of this study is to determine if the use of preimplantation genetic screening (PGS) by array comparative genomic hybridization (array CGH) and transfer of a single euploid blastocyst in patients with repeated implantation failure (RIF) can improve clinical results. Three patient groups are compared: 43 couples with RIF for whom embryos were selected by array CGH (group RIF-PGS), 33 couples with the same history for whom array CGH was not performed (group RIF NO PGS), and 45 good prognosis infertile couples with array CGH selected embryos (group NO RIF PGS). A single euploid blastocyst was transferred in groups RIF-PGS and NO RIF PGS. Array CGH was not performed in group RIF NO PGS in which 1-2 blastocysts were transferred. One monoembryonic sac with heartbeat was found in 28 patients of group RIF PGS and 31 patients of group NO RIF PGS showing similar clinical pregnancy and implantation rates (68.3% and 70.5%, resp.). In contrast, an embryonic sac with heartbeat was only detected in 7 (21.2%) patients of group RIF NO PGS. In conclusion, PGS by array CGH with single euploid blastocyst transfer appears to be a successful strategy for patients with multiple failed IVF attempts.